Flexible Robot Manipulators: Modelling, simulation and control - Tokhi, M.O; Tokhi, M.O; Azad, A.K.M (Control engineering series v.68, 2008)
The ever increasing utilisation of robotic manipulators for various applications in recent years has been motivated by the requirements and demands of industrial automation. Among these, attention is focused more towards flexible manipulators, due to various advantages they offer compared to their rigid counterparts. Flexural dynamics have constituted the main research challenge in modelling and control of such systems; research activities have accordingly concentrated on the development of methodologies to cope with this. The book reports recent and new developments in modelling, simulation and control of flexible robot manipulators. The material is presented in four distinct components: (i) a range of modelling approaches including classical techniques based on the Lagrange equation formulation, parametric approaches based on linear input/output models using system identification techniques, and neuro-modelling approaches; (ii) numerical modelling/ simulation techniques for dynamic characterisation of flexible manipulators using the finite difference, finite element, symbolic manipulation and customised software techniques; (iii) a range of open-loop and closed-loop control techniques based on classical and modern intelligent control methods including soft-computing and smart structures for flexible manipulators; and (iv) software environments for analysis, design, simulation and control of flexible manipulators. The book can serve as a teaching resource as well as a reference text for research.